The mitochondrial calcium uniporter regulates breast cancer progression via HIF‐1α. Issue 5 (4th April 2016) - Tosatto, Anna; Sommaggio, Roberta; Kummerow, Carsten; Bentham, Robert B; Blacker, Thomas S; Berecz, Tunde; Duchen, Michael R; Rosato, Antonio; Bogeski, Ivan; Szabadkai, Gyorgy; Rizzuto, Rosario; Mammucari, Cristina
Abstract: Triple‐negative breast cancer (TNBC) represents the most aggressive breast tumor subtype. However, the molecular determinants responsible for the metastatic TNBC phenotype are only partially understood. We here show that expression of the mitochondrial calcium uniporter (MCU), the selective channel responsible for mitochondrial Ca 2+ uptake, correlates with tumor size and lymph node infiltration, suggesting that mitochondrial Ca 2+ uptake might be instrumental for tumor growth and metastatic formation. Accordingly, MCU downregulation hampered cell motility and invasiveness and reduced tumor growth, lymph node infiltration, and lung metastasis in TNBC xenografts. In MCU‐silenced cells, production of mitochondrial reactive oxygen species (mROS) is blunted and expression of the hypoxia‐inducible factor‐1α (HIF‐1α) is reduced, suggesting a signaling role for mROS and HIF‐1α, downstream of mitochondrial Ca 2+ . Finally, in breast cancer mRNA samples, a positive correlation of MCU expression with HIF‐1α signaling route is present. Our results indicate that MCU plays a central role in TNBC growth and metastasis formation and suggest that mitochondrial Ca 2+ uptake is a potential novel therapeutic target for clinical intervention. Synopsis: MCU is the highly selective channel responsible for mitochondrial Ca 2+ uptake. MCU expression is shown here to correlate with breast cancer progression. Depletion of MCU reduces tumor growth and metastasis formation via suppression of ROS production and inhibition of HIF‐1α signaling. MCU expression correlates with breast tumor size and lymph node infiltration MCU silencing reduces TNBC cell migration and invasion MCU deletion reduces in vivo tumor growth and metastasis formation MCU silencing inhibits ROS–HIF‐1α signaling route Abstract : MCU is the highly selective channel responsible for mitochondrial Ca 2+ uptake. MCU expression is shown here to correlate with breast cancer progression. Depletion of MCU reduces tumor growth and metastasis formation via suppression of ROS production and inhibition of HIF‐1α signaling.